Whither ecological economics?. (1st January 2002) - Ozkaynak, Begum; Devine, Pat; Rigby, Dan
This paper examines the nature of ecological economics, arguing that it comprises two aspects, the qualitative framework within which it operates and the quantitative techniques which it uses to measure sustainability, evaluate policies and assist decision-making. The former is distinct to ecological economics, whereas the latter is largely shared with environmental economics. Although these have co-existed for some time, it is contended that the qualitative aspect needs to be developed if ecological economics is to realise its potential. The paper first offers a Schumpeterian "pre-analytic" vision of ecological economics. Ecological economics, it is argued, necessarily implies a fundamental change in the way problems are perceived and in how they should be addressed. Second, the paper discusses the quantitative aspect of ecological economics, arguing that the overlap with environmental economics in the techniques used is one reason why the two have frequently not been seen as sufficiently distinct. The paper concludes that a development of the qualitative, procedural aspect of ecological economics is needed if its full potential for influencing policy-making is to be realised.